CALIPER Hematology Reference Standards (I): Improving Laboratory Test Interpretation in Children (Beckman Coulter DxH 900–Core Laboratory Hematology System). Issue 3 (20th June 2020) - Tahmasebi, Houman; Higgins, Victoria; Bohn, Mary Kathryn; Hall, Alexandra; Adeli, Khosrow
Abstract: Objectives: Accurate hematologic test interpretation based on normative reference standards is critical to ensure appropriate clinical decision making. However, healthy pediatric reference data for most hematology parameters are lacking. To address this gap, this study establishes age- and sex-specific hematologic reference standards in the Canadian Laboratory Initiative on Pediatric Reference Intervals (CALIPER) cohort of healthy children and adolescents. Methods: Fresh whole blood samples collected from a total of 566 healthy children and adolescents (birth to <21 years) with informed consent were analyzed for 47 hematologic parameters on the Beckman Coulter DxH 900. Age- and sex-specific reference standards were calculated based on the Clinical and Laboratory Standards Institute guidelines. Results: Reference value distributions for most hematology parameters demonstrated dynamic changes across the pediatric age range with significant age-specific differences observed for 39 of the 47 parameters examined. Sex-specific differences were also observed for eight hematologic parameters, primarily during and after puberty. Conclusions: This study establishes a robust database of pediatric reference standards for 47 hematologic parameters in the CALIPER cohort for the first time. These comprehensive reference value data sets report potentially important and physiologically relevant trends in hematologic markers, clearly demonstrating the need for pediatric reference standards for hematologic test interpretation.